2023
DOI: 10.3389/fmed.2023.1233516
|View full text |Cite
|
Sign up to set email alerts
|

Impact of air pollution on healthcare utilization in patients with bronchiectasis

Hyun Lee,
Sang Hyuk Kim,
Sun-Kyung Lee
et al.

Abstract: IntroductionAir pollutants are increasingly recognized to affect long-term outcomes in patients with bronchiectasis. We aimed to figure out the association between air pollutants and the risk of healthcare utilization in patients with bronchiectasis.MethodsData for 1,029 subjects with bronchiectasis in Seoul were extracted. The air pollutants included particulate matter of 10 μm or less in diameter (PM10), particulate matter of 2.5 μm or less in diameter (PM2.5), sulfur dioxide (SO2), carbon monoxide (CO), ozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To establish COVID-19-naïve/COVID-19 vaccinated and unvaccinated groups, we We compared the incidence of ILD between vaccinated and unvaccinated individuals. ILD was defined using ICD-10 codes (J84.x, J67, J70, and D86), and comorbidities were defined based on a combination of past medical history, ICD-10 codes, and drug prescriptions [11].…”
Section: To the Editormentioning
confidence: 99%
“…To establish COVID-19-naïve/COVID-19 vaccinated and unvaccinated groups, we We compared the incidence of ILD between vaccinated and unvaccinated individuals. ILD was defined using ICD-10 codes (J84.x, J67, J70, and D86), and comorbidities were defined based on a combination of past medical history, ICD-10 codes, and drug prescriptions [11].…”
Section: To the Editormentioning
confidence: 99%
“…Participants’ BMIs were divided into the following groups: underweight (<18.5 kg/m 2 ), normal (18.5–22.9 kg/m 2 ), overweight (23.0–24.9 kg/m 2 ), and obese (≥ 25.0 kg/m 2 ) following the recommendations for Asians by the World Health Organization ( 36 ). The overall comorbidity load was evaluated using the Charlson Comorbidity Index (CCI) ( 37 , 38 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a study of 432 patients, G oeminne et al [ 65 ] found an 11.2% increased exacerbation risk associated with a 10 µg·m −3 increase in particulate matter particles <10 µm in diameter and a 4.7% increase per 10 µg·m −3 nitrogen oxide. Subsequent studies in Spain, China and Seoul have also shown a link between air pollutants, exacerbations and increased healthcare utilisation in bronchiectasis [ 66 68 ].…”
Section: The Pathophysiology Of Bronchiectasis Exacerbationsmentioning
confidence: 99%